High-efficiency laser-irradiation spheroidizing of NiCo2O4 nanomaterials - 刘培生 王浩 曾海波 范广明 刘亚鸿 (Optoelectronics letters, 2016)
We realized the desired spheroidizing of NiCo2O4 nanomaterials by laser irradiating NiCo2O4 suspensions with different concentrations. The results reveal that the as-prepared samples are desired spheres with the maximal average size of 568 nm and the superior dispersity, which were obtained at the energy density of 0.30 J·pulse^-1·cm^-2 and NiCo2O4 suspension concentration of 0.2 mg·mL^-1. However, the phase segregation, which was induced by large amounts of solid redox of Co^3＋/Co^2＋ and Ni^3＋/Ni^2＋, also appears in the laser-irradiation process.